2010
DOI: 10.1002/aic.12041
|View full text |Cite
|
Sign up to set email alerts
|

Absorber intercooling in CO2 absorption by piperazine‐promoted potassium carbonate

Abstract: in Wiley InterScience (www.interscience.wiley.com).Intercooling was evaluated as a process option in CO 2 absorption by piperazine (PZ) promoted potassium carbonate. The system performance with 4.5 m K þ /4.5 m PZ was simulated by a model in Aspen PlusThe absorber was evaluated for use with a double matrix stripper by optimizing the position of the semilean feed and intercooling stages to maximize CO 2 removal. Additionally, a simple absorber system was modeled to observe the effect of intercooling on systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…Over the past decades, many emerging process configurations have been developed to reduce the energy consumption and capital cost for CO 2 capture. The absorber coupled with an intercooler (i.e., intercooling) can lower absorption temperature and enhance absorption capacity due to a new thermodynamic equilibrium being reached (Chang and Shih, 2005;Karimi et al, 2011;Kvamsdal et al, 2009;Oexmann et al, 2008;Plaza et al, 2010). However, it should be noted that the lower temperature will decrease the CO 2 absorption rate.…”
Section: Developed Process Configurations For Post Combustion Co 2 Camentioning
confidence: 95%
“…Over the past decades, many emerging process configurations have been developed to reduce the energy consumption and capital cost for CO 2 capture. The absorber coupled with an intercooler (i.e., intercooling) can lower absorption temperature and enhance absorption capacity due to a new thermodynamic equilibrium being reached (Chang and Shih, 2005;Karimi et al, 2011;Kvamsdal et al, 2009;Oexmann et al, 2008;Plaza et al, 2010). However, it should be noted that the lower temperature will decrease the CO 2 absorption rate.…”
Section: Developed Process Configurations For Post Combustion Co 2 Camentioning
confidence: 95%
“…A model was developed to illustrate the mechanism of gas-liquid mass transfer with reactions in RPB (Yi et al, 2009). Intercooling of the absorber column for piperazine-promoted PC solution increased the CO 2 removal by 10% with the double matrix configuration (Plaza et al, 2010). In a different study, Zhao et al (2011) compared the effect of some types of packing on the mass transfer enhancement in a laboratory scale absorber column of PC process.…”
Section: Absorber Columnmentioning
confidence: 99%
“…Aqueous monoethanolamine (MEA) has traditionally been the benchmark solvent for post combustion CO 2 capture, and various other primary and secondary alkanolamines (including those sterically hindered) have been investigated for performance improvements over MEA (Rochelle, 2009;Freguia and Rochelle, 2003;Oyenekan and Rochelle, 2006;Freeman et al, 2010a;Ma'mun et al, 2007;Idem et al, 2006). Conventional amine-based absorption processes are energy tion into potassium carbonate/bicarbonate (K 2 CO 3 /KHCO 3 , or PCB) solutions promoted with piperazine (Plaza et al, 2010;Oyenekan and Rochelle, 2009;Cullinane and Rochelle, 2006). They have reported that the promoted PCB solutions possessed greater absorption rates and capacities than those of 7 M MEA at the typical flue gas temperatures (Oyenekan and Rochelle, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this process, the CO 2 is absorbed into a high-concentration PCB solution (40 wt%) at an elevated temperature (70-80 • C). Since the rate of CO 2 absorption into the PCB solution is slow even at an elevated temperature, a promoter or catalyst is required to accelerate the rate (Plaza et al, 2010;Zhang et al, 2011;Lu et al, 2013). The CO 2 loadings of the lean and rich solutions in the absorber are equivalent to 15-20% and 40-45% carbonate-to-bicarbonate conversion, respectively, which allows to achieve a 90% CO 2 removal rate from coal combustion flue gas based on the vapor-liquid equilibrium data (Tosh et al, 1959).…”
Section: Introductionmentioning
confidence: 99%